2020
DOI: 10.1155/2020/5687672
|View full text |Cite
|
Sign up to set email alerts
|

The Neutrophil Percentage‐to‐Albumin Ratio Is Associated with All‐Cause Mortality in Critically Ill Patients with Acute Kidney Injury

Abstract: Background. There is no evidence to suggest the predictive power of neutrophil percentage-to-albumin ratio (NPAR) in patients with acute kidney injury (AKI). We hypothesized that NPAR would correlate with all-cause mortality in critically ill patients with AKI. Methods. From the MIMIC-III V1.4 database, we extracted demographics, vital signs, comorbidities, laboratory tests, and other clinical data. The clinical endpoints were 30-, 90- and 365-day all-cause mortality in critically ill patients with AKI. Cox pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 40 publications
4
37
0
Order By: Relevance
“…In this study, we found that lower albumin levels on admission can predict the outcome of COVID‐19 independent of other known indicators such as lymphocyte count or comorbidities 3 . This result is consistent with a previous study reporting hypoalbuminemia or decline of albumin, which is associated with the severity of ARDS 23 or acute kidney injury 24 . A meta‐analysis showed that about 80.4% of patients with abnormal liver function in COVID‐19 had hypoalbuminemia, which was associated with prognosis and outcome 25…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that lower albumin levels on admission can predict the outcome of COVID‐19 independent of other known indicators such as lymphocyte count or comorbidities 3 . This result is consistent with a previous study reporting hypoalbuminemia or decline of albumin, which is associated with the severity of ARDS 23 or acute kidney injury 24 . A meta‐analysis showed that about 80.4% of patients with abnormal liver function in COVID‐19 had hypoalbuminemia, which was associated with prognosis and outcome 25…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were consistent with the results of studies that evaluated the prognostic value of NPARs in other clinical settings including STEMI [ 16 ], acute kidney injury [ 17 ], septic shock [ 18 ], rectal cancer [ 19 ], and palliative pancreatic cancer [ 20 ]. Additionally, several studies have investigated other measurable laboratory markers related to the inflammatory response in CS.…”
Section: Discussionsupporting
confidence: 90%
“…One recent study showed that hypoalbuminemia was a frequent finding early in CS and was associated with mortality independent of other risk factors [ 15 ]. Recently, several studies have combined these two markers and found that the neutrophil percentage-to-albumin ratio (NPAR) could serve as an inflammation-based prognostic predictor in patients with STEMI [ 16 ], acute kidney injury [ 17 ], septic shock [ 18 ], rectal cancer [ 19 ], or palliative pancreatic cancer [ 20 ]. Nevertheless, to the best of our knowledge, no previous study has explored the prognostic value of NPARs in critically ill patients with CS.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis has shown that about 80.4% of COVID-19 patients with abnormal liver function had hypoalbuminemia, associated with a poor prognosis and outcome [ 23 ]. Moreover, hypoalbuminemia has also been associated with the severity of acute respiratory distress syndrome [ 24 ] and acute kidney injury [ 25 ].…”
Section: Discussionmentioning
confidence: 99%